(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Introduction: The Coronavirus Disease 2019 (COVID-19) pandemic has presented an unparalleled challenge to healthcare systems worldwide since its emergence in late 2019. As health-care providers grapple with the complexities of managing COVID-19 patients, the need for comprehensive understanding of treatment strategies and drug utilization patterns becomes increasingly critical. In response to the evolving nature of the pandemic, health-care facilities have implemented various therapeutic interventions, often adapting treatments based on emerging evidence and clinical experience. This manuscript presents a retrospective observational drug utilization study conducted at a tertiary care teaching hospital, aimed at examining the patterns of drug utilization among COVID-19 patients. With the rapid development and dissemination of treatment guidelines and protocols, understanding real-world drug utilization patterns is essential for optimizing therapeutic approaches and informing evidence-based clinical decision-making. Ultimately, this research aims to contribute to the collective efforts to mitigate the impact of the COVID-19 pandemic and improve outcomes for patients receiving care at tertiary care teaching hospitals. Objective: The objective of the study is to analyze prescribing patterns in COVID-19 patients and to find the prevalence of co-morbidities associated with COVID-19. Methods: A total of 500 patients diagnosed with COVID-19 were finally recruited after strictly obeying the selection criteria in this retrospective, observational study conducted over 6 months in a tertiary care teaching hospital, Parul Sevashram Hospital. Relevant data were extracted from prescriptions, case records, and investigational reports. Results: Of the total 500 patients, 300 (60%) were males and 200 (40%) females. The highest numbers of patients were in the age group of 46–55 years (147 patients, 29.34%). Out of 500, 289 patients had comorbidity in which hypertension was the most common comorbidity (115 patients, 39.8%) observed, followed by diabetes (102 patients, 35.3%) and diabetes mellitus plus hypertension (52 patients, 18%). Commonly employed in treatment were class of medications such as anticoagulant (9.3%), antipyretic (8.7%), folic acid supplements (8.4%), Vitamin C supplements (8.4%), proton pump inhibitors (8.3%), Vitamin D supplements (8.1%), steroids (7.7%), and antibiotics (7.6%), while other classes of drugs such as anthelmintics, antitussive, antiviral, and antihypertensive were administered according to the patient’s specific disease state and the severity of their condition. Conclusion: Further investigation is warranted on the evolving subject of COVID-19 due to the virus’s variability and characteristics, alongside the insufficient evidence backing current treatment drugs for the development of updated guidelines, ultimately lessening the strain on global health-care providers. Future research endeavors will focus on refining drug utilization and prescription practices for COVID-19 treatment. Regular evaluation of drug utilization patterns is imperative for enhancing management strategies and the overall quality of life for patients.